The Application of a Cooperative Learning Model to Increase The Activeness and Learning Outcomes of Mathematics in class VI Elementary School - Eni Sri Utami (Universitas Sebelas Maret, 2022)
This research is a Classroom Action Research which is carried out with the aim of applying a cooperative learning model to improve students' activeness and learning outcomes in mathematics for the material of building a spherical space for class VI SD Negeri 3 Senenan in semester 2 of the 2021/2022 academic year. This research was conducted at SD Negeri 3 Senenan. This Classroom Action Research was conducted in 2 cycles, each cycle consisting of the planning stage, implementation stage, data collection stage, and reflection stage. The research subjects were all VI grade students of SD Negeri 3 Senenan in semester 2 of the 2021/2022 academic year, totaling 25 students consisting of 12 male and 13 female students. The data collection technique is to compare the test scores obtained in the initial condition of the test scores after cycle I and the test scores after cycle II. The results of this study showed an increase from the initial condition of an average of 6.36 to 7.2 in cycle I and to 8.08 in cycle II. So it can be concluded that student activeness has increased, and learning outcomes have increased. Thus, the use of a cooperative learning model can increase the activeness and learning outcomes of mathematics on the material of building a spherical space for class VI SD Negeri 3 Senenan in semester 2 of the 2021/2022 academic year.